Persistence of major socio-economic inequalities in childhood measles–mumps–rubella vaccination coverage and timeliness under vaccination mandates, France, 2015 to 2024 - Pierre Verger (Eurosurveillance)
Introduction Since the late 2000s, several major measles epidemics have occurred in Europe, including France. In 2017, the French Health Ministry extended from three to 11 the number of mandatory childhood vaccines required for preschool and primary school admission; these included the vaccine against measles, mumps and rubella (MMR). Aim Our aim was to assess if this measure helped to improve MMR vaccine timeliness (VT) or reduce socioeconomic inequalities in MMR vaccine coverage. Methods A nationwide study of three birth cohorts (2015, 2017, 2019) followed up 2.1 million children for 48 months to assess the course of the timeliness of MMR vaccine dispensation, before and after it became mandatory in France (January 2018). Data came from the French national health insurance fund drug reimbursement database. Results Despite improvements from 2015 to 2019, pharmacies dispensed MMR vaccines late for 33% of children in the 2019 cohort (mean cumulative delay compared with recommended dates: 7.1 months). Vaccines for children from low-income families were dispensed later (mean delay of at least +1 month) than those from higher-income families. The 2019 cohort did not reach the 95% WHO target of two MMR doses at 24 months of age, nor at 48 months. Discussion With measles intensifying worldwide, these vaccination delays and inequalities may contribute to the resurgence of epidemics. In addition to vaccination mandates, an ambitious public health policy is needed to reduce inequalities in access to vaccination and to improve parents’ vaccine acceptance through educational strategies.